Investigations of the first-wall erosion of DEMO with the CELLSOR code. (August 2017) - Beckers, M.; Biel, W.; Tokar, M.; Samm, U.
Highlights: CELLSOR: introduction of PWI aspects into DEMO system code studies (being focused on global equilibrium studies). Benchmarked with well-established and sophisticated code EIRENE. Erosion of a W-wall calculated for (damage by wall-recycled and) recharged neutrals (D, T) and by (ions)(D, T, He, N, W). Investigation of strong and weak diffusive and convective radial transport (within the SOL), and high and low upstream separatrix densities. The wall clearance Δ SOL (main-chamber) (needs to be at least 14-25 cm on DEMO (depending on SOL-parameters) for tolerable erosion levels. Abstract: Fusion reactor systems codes (SCs) are 0.5d codes used for optimization studies towards the design of a tokamak demonstration power plant (DEMO). These codes usually comprise a description of the core plasma physics, technology aspects and reactor economy, while only a coarse description of plasma-wall interaction (PWI) aspects is included. Therefore, the new systems code extension CELLSOR (Code to Estimate the Lifetime Limited by Sputtering Of a Reactor wall) was developed in order to allow inclusion of PWI effects into reactor optimization studies. CELLSOR is foreseen to be used as a secondary tool for PWI evaluations, taking design point parameters from the European PROCESS systems code as input. CELLSOR consists of an analytical treatment of the plasma in the scrape-off layer (SOL) for fuel ions (D, T), solving the 1.5d continuity equation in fluid approximation to obtain perpendicular flux and ion density in the SOL, and a fast Monte-Carlo description of the neutral particle (D, T) behavior. The Monte Carlo (MC) implementation of the new code extension was successfully benchmarked with results from the EIRENE code. The trajectories of eroded neutral W were computed within CELLSOR ERO, an add-on code used for calculations of prompt re-deposition and self-sputtering. The damage by ions was calculated analytically for fuel (D, T), ash (He), seeding gas (N) and wall material (W), including the acceleration by a sheath in front of the wall, assuming radially constant impurity concentrations. Six exemplary DEMO SOL test-cases were defined, covering the range of predicted diffusive and convective transport strength within the SOL, and of upstream separatrix density levels sufficient for detached diverter conditions. The damage by ions (D, T, He, N, W) and by hot neutrals (D, T), being born by charge-exchange within the hot pedestal region ( Δ T = − 300 eV / cm), was compared for the six cases. The results indicated, that in the investigated low density and weak transport cases, the recharged neutrals caused the major threat to the FW due to bad SOL screening ability, i.e. deeper plasma penetration for neutrals. In the other cases, N ions were the dominant driver for erosion due to their high concentration levels and strong sheath acceleration. Furthermore, the net erosion, incl. prompt re-deposition and self-sputtering, was investigated for variations of the wall clearance Δ SOL, which was identified as the main control parameter to keep the FW erosion in the main chamber below acceptable levels. Within the intermediate reference case, i.e. medium transport ( D ⊥ = 0.5 m 2 s − 1, v ⊥ = 5 m s − 1 ), the net erosion rate was acceptable, if the wall clearance was at least Δ SOL ≥ 14 cm, whereas a clearance of Δ SOL ≈ 25 cm was sufficient within all 6 investigated test-cases.